2008
DOI: 10.1111/j.1365-2036.2008.03671.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between symptom load of gastro‐oesophageal reflux disease and health‐related quality of life, work productivity, resource utilization and concomitant diseases: survey of a US cohort

Abstract: SUMMARY BackgroundAnalysis of the burden of gastro-oesophageal reflux disease (GERD) in relation to the severity and frequency of symptoms is essential to identify individuals and groups in whom targeted management is justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
2
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 29 publications
4
75
2
10
Order By: Relevance
“…For individual patients, the presence or absence of erosions may not be of much relevance in symptom generation, since all participants agreed that the impact of the reflux symptoms on QoL appears as substantial in NERD patients as it is in patients with ERD [12]. …”
Section: Clinical Features Of Nerdmentioning
confidence: 99%
“…For individual patients, the presence or absence of erosions may not be of much relevance in symptom generation, since all participants agreed that the impact of the reflux symptoms on QoL appears as substantial in NERD patients as it is in patients with ERD [12]. …”
Section: Clinical Features Of Nerdmentioning
confidence: 99%
“…This study demonstrated that the severity and frequency of symptoms lowered the QoL and productivity of GERD patients (17), and the severity of symptoms was related more to QoL than was the frequency of symptoms (18). Existing studies of QoL focused mostly on classical symptoms, but there have also been studies related to atypical symptoms and the QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Распро-страненность ГЭРБ в странах Западной Европы и Северной Америки составляет 10-20%, в странах Азии -5%, в России -13,3%, с тенденцией к росту [2]. ГЭРБ отнесена к основным популяционно-зна-чимым заболеваниям, в наибольшей степени ухуд-шающим качество жизни человека: согласно про-веденным исследованиям в США, качество жизни у больных с ГЭРБ снижено до 80% [3]. Примерно у трети больных ГЭРБ выявляется воспаление дис-тального отдела пищевода (рефлюкс-эзофагит).…”
Section: актуальностьunclassified